2020
DOI: 10.1002/brb3.1954
|View full text |Cite
|
Sign up to set email alerts
|

Task‐based functional connectivity in aging: How task and connectivity methodology affect discovery of age effects

Abstract: Introduction Past studies have found that healthy aging has a significant effect on the organization and function of networks in the human brain. Many of these studies have examined how functional connectivity during one task or at rest is affected by aging; however, few studies have systematically examined how the effect of age on functional connectivity may vary as a function of choice of in‐scanner task. Methods The present study included healthy adults between the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
0
13
1
Order By: Relevance
“…Cardiovascular health scores were coded as poor=0, intermediate=1, and optimal=2 according to the American Heart Association recommendations and considering pharmacological treatment (for cut-off definitions see Supplementary Table 7b) 24 . All seven cardiovascular traits were measured at baseline (on average 7.6 [range: [4][5][6][7][8][9][10][11][12] years prior to brain imaging) and five traits were measured at the time of brain imaging, not including blood cholesterol and glycaemic status (blood was drawn only at baseline). All statistical models were adjusted for age, age 2 , sex, education, GM volume, WMH, head motion during fMRI, assessment centre (only for UK Biobank) and signal-to-artefact ratio (only for Rotterdam Study).…”
Section: Genetic Correlations Between System Segregation and Cardiovascular Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular health scores were coded as poor=0, intermediate=1, and optimal=2 according to the American Heart Association recommendations and considering pharmacological treatment (for cut-off definitions see Supplementary Table 7b) 24 . All seven cardiovascular traits were measured at baseline (on average 7.6 [range: [4][5][6][7][8][9][10][11][12] years prior to brain imaging) and five traits were measured at the time of brain imaging, not including blood cholesterol and glycaemic status (blood was drawn only at baseline). All statistical models were adjusted for age, age 2 , sex, education, GM volume, WMH, head motion during fMRI, assessment centre (only for UK Biobank) and signal-to-artefact ratio (only for Rotterdam Study).…”
Section: Genetic Correlations Between System Segregation and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…High within-network connectivity but low betweennetwork connectivity, called system segregation, is a key global feature associated with higher cognitive performance across the life-span 3,4 . During aging and disease, system segregation decreases 3,[5][6][7][8][9] (for review see 10,11 ), resulting in poorer cognitive functions 3,5,9,[12][13][14]15 (for review see 4 ). In contrast, relatively preserved system segregation enhances cognitive resilience to brain alterations in older adults 16 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study in our group found that the nature of the in-scanner task had a significant effect on discovery of age effects on connectivity metrics, with these effects appearing to be more evident during tasks of fluid reasoning than during tasks of episodic memory. 14 Further, in-scanner task performance showed a variety of relationships between fluid reasoning task performance and connectivity within/between networks during these tasks, suggesting that at least some variability in task performance was accounted for by these measures. While this study did not directly compare these patterns to those observed at rest, it shows that task selection can have a strong effect on the presence and magnitude of the effects of age on functional connectivity.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, there is evidence for changes in the FC pattern with increasing age. The consensus of aging studies indicates a decrease in FC within resting state (RS) networks such as the default mode network (DMN) or the salience network (SN) 28 31 , concomitant with an increase in FC between the different networks 28 , 32 , 33 as well as a general association of aging with reduced global efficiency and modularity 34 . Moreover, Esposito et al 35 described a reduction of the physiological anticorrelation activity between the DMN and the DAN in RS as part of a normal aging process and MCI as a status in which these changes are even more pronounced.…”
Section: Introductionmentioning
confidence: 99%